Attachment security, verbal ability, and inhibitory control in middle childhood - Anna Kamza; Adam Putko (BMC Psychology, 2021)
Abstract Background The relationship between parent–child attachment and executive function (EF) in middle childhood remains relatively poorly studied. Very little is known about the role that the child’s verbal ability might play in these relationships. Therefore, in the present study, we explored the concurrent links between perceived attachment security with parents and hot and cool inhibitory control (IC)—a core component of EF—as well as the potential mediating role of verbal ability in those links. Methods The participants were 160 children aged 8 to 12 (51% girls). They completed the Attachment Security Scale, the computerised version of the go/no-go task, the delay discounting task, and the vocabulary subtest from the Wechsler Intelligence Scale for Children. Pearson’s correlations were conducted to test relationships between the study variables. A hierarchical multiple linear regression analysis was performed to examine whether attachment security uniquely contributed to the outcomes after accounting for covariates. The indirect effects were tested using a non-parametric resampling bootstrap approach. Results The results showed that, after accounting for the child’s age and sex, there was a direct relationship between attachment security with the father and cool, but not hot, IC. However, there were no significant links between attachment security with the mother and both aspects of IC. We also found that children’s verbal ability played a mediating role in the associations between both child–father and child–mother attachment security and hot, but not cool, IC above and beyond the child’s age. Conclusions The current study extends previous work on executive functions in middle childhood. The results highlight the role of attachment in explaining individual differences in IC in middle childhood as well as the different mechanisms through which attachment with parents might explain cool vs. hot IC. The findings have potential implications for therapeutic interventions using the family context as a target to improve IC in middle childhood.